Functional diversity in coral-dinoflagellate symbiosis - Stat, Michael; Morris, E.; Gates, R. (National Academy of Sciences, 2008)
Symbioses are widespread in nature and occur along a continuum from parasitism to mutualism. Coral-dinoflagellate symbioses are defined as mutualistic because both partners receive benefit from the association via the exchange of nutrients. This successful interaction underpins the growth and formation of coral reefs. The symbiotic dinoflagellate genus Symbiodinium is genetically diverse containing eight divergent lineages (clades A-H). Corals predominantly associate with clade C Symbiodinium and to a lesser extent with clades A, B, D, F, and G. Variation in the function and interactive physiology of different coral-dinoflagellate assemblages is virtually unexplored but is an important consideration when developing the contextual framework of factors that contribute to coral reef resilience. In this study, we present evidence that clade A Symbiodinium are functionally less beneficial to corals than the dominant clade C Symbiodinium and may represent parasitic rather than mutualistic symbionts. Our hypothesis is supported by (i) a significant correlation between the presence of Symbiodinium clade A and health-compromised coral; (ii) a phylogeny and genetic diversity within Symbiodinium that suggests a different evolutionary trajectory for clade A compared with the other dominant Symbiodinium lineages; and (iii) a significantly lower amount of carbon fixed and released by clade A in the presence of a coral synthetic host factor as compared with the dominant coral symbiont lineage, clade C. Collectively, these data suggest that along the symbiotic continuum the interaction between clade A Symbiodinium and corals may be closer to parasitism than mutualism. © 2008 by The National Academy of Sciences of the USA.